Parapentaneura bentogomensis gen. n., sp. n., a new Tanypodinae (Diptera, Chironomidae) from Brazil - Stur, Elisabeth; Fittkau, Ernst Josef; Serrano, Mirian A. Da Silva (Zootaxa, 2006)
Parapentaneura bentogomensis gen. n., sp. n., from Mato Grosso, Brazil is diagnosed and described as larva, pupa and adult male. The pupa and larva of an additional species in Parapentaneura gen. n. is described, but not formally named. The new genus belongs to the tribe Pentaneurini of the subfamily Tanypodinae and is morphologically most similar to the genera Pentaneura, Larsia and Hudsonimyia.